Evaluation of the Therapeutic Effect of 15 ppm Silver Nanoparticle Spray Compared to Clotrimazole 1% on Candida Vaginitis: A Randomized Controlled Clinical Trial - Maryam Aghaei; Maryam Kianpour; Farahnaz Mardanian; Farnoosh Farahbod; Fariba Fahami; Mehdi Ghahremantermeh (Tehran University of Medical Sciences, 2023)
Objective: In vitro and in vivo researches have shown that silver nanoparticles have more antimicrobial properties with a lower concentration than antifungal agents against candida vaginitis. Therefore, this study evaluated the therapeutic effect of silver nanoparticles (Nivasha spray15ppm) compared to clotrimazole 1% vaginal cream on candida vaginitis. Materials and methods: In this clinical trial study, 110 women with confirmed candida vaginitis randomly were divided into test (n=58) and control (n=52) groups. Silver nanoparticles spray with an applicator (Nivasha 15 ppm), and clotrimazole 1% were administered to test and control groups, respectively. Then, within ten days, post-intervention checkup and patient self-reported for treatment results were recorded in checklists and the data were analyzed statistically. Results: The improvement rate in test group (98.0%) was 1.44 times higher than in control (67.9%). Moreover, disease symptoms after the intervention (including unusual secretions, itching and burning, redness) in test group were significantly less than in the control, but there was no significant difference in the ratio of edema in two groups) p=0.071(. Furthermore, the average recovery time (days) of all symptoms in test group was lower than control (p<0.05). Finally, the rate of patients' satisfaction with the treatment process in the test group (76.9%) was more than control (46.6%) (p=0.004). Conclusion: Nivasha spray had more effectiveness compared to the clotrimazole 1%. Therefore, it can be used as an alternative drug in the treatment of Candida vaginitis.